Islamic Perspectives on Cybersecurity and Data Privacy: Legal and Ethical Implications - Koko Komaruddin; Andrew Shandy Utama; Eko Sudarmanto; Sugiono Sugiono (West Science Law and Human Rights, 2023)
In the rapidly evolving landscape of cybersecurity and data privacy, the interface between culture, ethics, and law plays a pivotal role. This study delves into "Islamic Perspectives on Cybersecurity and Data Privacy: Legal and Ethical Implications" to investigate how Islamic principles and values intersect with contemporary cybersecurity practices. Combining qualitative content analysis of Islamic texts with a quantitative survey, the research reveals a strong alignment between Islamic principles and modern cybersecurity norms, particularly in areas of privacy, honesty, and the prevention of harm. However, it also highlights the legal and ethical challenges that arise, such as reconciling the prohibition of 'gharar' and addressing the intersection of Islamic finance with digital transactions. The findings emphasize the need for inclusive and culturally sensitive approaches to cybersecurity, informed by a deeper understanding of Islamic ethics and jurisprudence.